The influence of facebook on students’ attitudes in accordance with law No. 19 of 2016 - Tara Ashiilah; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Benni Sitanggang; Retno Rezky Fajriana; Ernes Tifani Anastasia br Saragih; Marina Gabriella (Institute of Computer Science (IOCS), 2023)
The development of information technology and social media has significantly impacted the social behavior of adolescents. One concerning issue is the proliferation of hate speech on Facebook. This research focuses on the impact of hate speech on Facebook on students at the Private National Heroes Middle School in Medan. The method used in this research is qualitative descriptive, involving interviews. The research findings present the impact of hate speech on social media, aiding in understanding the influence of social media on adolescents. This is essential for guiding students in the responsible and ethical use of social media. The research can serve as a basis for further studies and contribute to a safer social media environment for adolescents. It addresses the knowledge gap regarding the impact of hate speech on social media on the behavior of students in the digital era.